ENGLISH AS A LINGUA FRANCA: IMPLICATIONS FOR PEDAGOGY AND ASSESSMENT - Fang, Fan (Gabriel) (TEFLIN Journal, 2017)
The English language functions as a global language that facilitates communication among people of different lingua-cultures. This background leads to the question of whether the traditional language assessment still fulfils the needs of the majority of language learners who will use English for various purposes with people from different linguistic and cultural backgrounds. This article illustrates the development and spread of the English language by focusing on two key paradigms: World Englishes (WE) and English as a lingua franca (ELF). This article argues that a native-oriented means of English pedagogy and assessment does not fit the current functions of the language and cannot meet the various and complex needs of the majority of English language learners. It therefore emphasizes the importance of an ELF-informed approach, such as the ‘post-method' approach to English language teaching and more flexible language assessment focusing on students' performance of tasks. The article concludes that English language teaching and assessment need to be more informed by ELF than by the entrenched, anachronistic native-oriented ideology.